2011
DOI: 10.1021/ma102547q
|View full text |Cite
|
Sign up to set email alerts
|

Counterion Dynamics in Polyester−Sulfonate Ionomers with Ionic Liquid Counterions

Abstract: Conventional sodium cations (Na+) in sulfonated polyester ionomers were replaced with ammonium-based ionic liquid counterions. Counterion dynamics were measured by dielectric spectroscopy and linear viscoelastic response via oscillatory shear. Ion exchange from sodium counterions to ionic liquid counterions such as tetramethylammonium and tetrabutylammonium showed an order of 104 increase in conductivity compared with sodium counterions, primarily attributed to weaker ionic interactions that lower the glass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
108
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 60 publications
(127 reference statements)
12
108
1
Order By: Relevance
“…This corresponds to the mid-point of the glass transition temperature T g , and the onset for this transition was estimated as 56 C. This is significantly lower than the T g s reported for a previous series of Nacontaining PAMPS-based ionomers recently studied by our group (93 C for a co-polymer of PAMPS and poly(vinyl sulfonate) with Na + and N 1222 in a 2:8 ratio [31], 133 C for a PAMPS homopolymer also with Na and N 1222 in a 2:8 ratio [32]). This can be attributed to the larger co-cation, which has the effect of lowering T g by reducing the number of cross-links as demonstrated by Colby and co-workers [23,24]. The broad nature of the transition is indicative of sample inhomogeneity, and is also consistent with previous PAMPS ionomers studied by our group.…”
Section: Thermal Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…This corresponds to the mid-point of the glass transition temperature T g , and the onset for this transition was estimated as 56 C. This is significantly lower than the T g s reported for a previous series of Nacontaining PAMPS-based ionomers recently studied by our group (93 C for a co-polymer of PAMPS and poly(vinyl sulfonate) with Na + and N 1222 in a 2:8 ratio [31], 133 C for a PAMPS homopolymer also with Na and N 1222 in a 2:8 ratio [32]). This can be attributed to the larger co-cation, which has the effect of lowering T g by reducing the number of cross-links as demonstrated by Colby and co-workers [23,24]. The broad nature of the transition is indicative of sample inhomogeneity, and is also consistent with previous PAMPS ionomers studied by our group.…”
Section: Thermal Analysissupporting
confidence: 87%
“…Colby et al [23,24] have demonstrated the effects of various organic IL cations in sulfonated polyester ionomers and sulfonated polystyrene. They demonstrated that the partial substitution of bulky IL quaternary ammonium cations into polymeric materials resulted in a significant reduction in T g and a subsequent improvement in ionic conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, research on actuators comprising ionic liquids has commonly used a few conventional polymers 25,26 , thus impeding major advances in ionic polymer actuators, which essentially require the optimization of ion transport characteristics and mechanical properties of the polymer layer. In this respect, the use of microphase-separated polymers in actuators has recently been proposed as a promising means to elevate the actuator performance 7,10,[33][34][35][36][37][38][39][40][41] . For instance, Long et al 34,35 , Spontak et al 7,36,37 , Colby et al 38,39 and Watanabe et al 10,40 , have employed self-assembled block copolymers in actuators and improved electromechanical deformation has been reported, compared with that of several conventional polymers lacking organization.…”
mentioning
confidence: 99%
“…It is important to note that ionomers with large counter ions form few or no ion aggregates and show plasticizing effect to decrease the terminal relaxation time. 15) Although P(VI/C 2 TFSI) possesses a large counter anion, the low amount of TFSI − ions in the P(VI/C 2 TFSI) with low x q Fig. 4.…”
Section: Viscoelastic Master Curvesmentioning
confidence: 99%
“…This is consistent with ionomer systems with larger counter ions studied by Colby and his coworkers. 15) According to their ionomer research, T g values of ionomers decrease with increasing counter ion size because larger counter ions act as plasticizers. Since the volume fraction of the TFSI − ion can be as high as 0.50 in the PC 2 TFSI monomer unit, 9) it is reasonable for TFSI − ions to act as plasticizers in the bulk P(VI/C 2 TFSI).…”
Section: Glass Transition Temperaturementioning
confidence: 99%